Analisa Strategi Pengembangan UKM Sosis Sumijaya Ditinjau dari Aspek Pemasaran dan Aspek Keuangan - Eny Setyariningsih (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
The development of Small and Medium Enterprises (SMEs) is a very important action to advance the economy of a country, including Indonesia. Sumi Jaya Sausage UKM is one of the Small Medium Enterprises in the Regency area. Mojokerto which produces various types of sausages is then marketed to various places such as school canteens, Islamic boarding schools and traditional schools. But all that is still on a small scale both in terms of marketing and finance. Therefore it is necessary to develop in order to become a successful SME in the future. The purpose of this study was to determine the development strategy of Sumi Jaya Sausage SMEs in terms of marketing aspects and financial aspects. The method used in this study is qualitative methods and quantitative methods. Where is the qualitative method to analyze the marketing aspects and quantitative methods to analyze financial aspects. Then the results of the analysis are tested using SWOT analysis to find out the development strategies that match the condition of the UKM. The results of the analysis obtained on the marketing aspects and financial aspects show that Sumi Jaya Sausage SMEs are worthy to be developed. And from the results of the SWOT analysis shows that the strategy that should be applied by Sumi Jaya Sausage SMEs is the SO strategy (Strengths-Opportunities). The SO strategy is a strategy that uses the power to make the most of opportunities.